Why did Prophet Muhammad Sallallahu Alayhi Wa Sallam Marry Aisha at the Age of 9 Years Old? - Guru Dev Teeluckdharry (Al-Arfa: Journal of Sharia, Islamic Economics and Law, 2025)
According to many Jewish, Christian, and Hindu opponents of Islam, Prophet Muhammad Sallallahu Alayhi Wa Sallam (The Last and Final Prophet of Islam - Peace Be Upon Him) was a sexual pervert and pedophile because he was betrothed to Aisha at the age of 6 years old and married her at the age of 9 years old which is the age of puberty following consummation of the marriage. Many Muslim Scholars, Ulemas, Mawlanas, and Clerics have refuted such a blasphemous allegation through the statement that the marriage of Aisha with Prophet Muhammad Sallallahu Alayhi Wa Sallam (The Last and Final Prophet of Islam - Peace Be Upon Him) occurred due to a Divine Inspiration from ALLAH, The Most Merciful and Most Gracious who knows best.